Single-Tube Genotyping without Oligonucleotide Probes - Germer, Søren; Higuchi, Russell

(untitled) (Genome Research, 1999)
We report the development of a self-contained (homogeneous), single-tube assay for the genotyping of single-nucleotide polymorphisms (SNPs), which does not rely on fluorescent oligonucleotide probes. The method, which we call T m-shift genotyping, combines allele-specific PCR with the discrimination between amplification products by their melting temperatures (T m). Two distinct forward primers, each of which contains a 3′-terminal base that corresponds to one of the two SNP allelic variants, are combined with a common reverse primer in a single-tube reaction. A GC-tail is attached to one of the forward allele-specific primers to increase theT m of the amplification product from the corresponding allele. PCR amplification, T manalysis, and allele determination of genomic template DNA are carried out on a fluorescence-detecting thermocycler with a dye that fluoresces when bound to dsDNA. We demonstrate the accuracy and reliability ofT m-shift genotyping on 100 samples typed for two SNPs, and recommend it both as a simple and inexpensive diagnostic tool for genotyping medically relevant SNPs and as a high-throughput SNP genotyping method for gene mapping.